Muatan Profil Pelajar Pancasila dalam Serat Wedhatama Karya KGPAA Mangkunegara IV Pupuh Pangkur - Mohamad Makincoiri; Agatia Mega Rianda; Angga Bimo Satoto (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Serat Wedhatama is one of the literary works that contains moral values that are still relevant to social life and in accordance with the Profil Pelajar Pancasila. The purpose of this study is to describe the related to the Profil Pelajar Pancasila’s in the serat Wedhatama. This is a qualitative descriptive research. The data were collected by reading and note-taking method, and then analyzed by qualitative analysis method of Miles and Huberman model. The results of this study indicated that the Profil Pelajar Pancasila dimensions implied in the serat Wedhatama pupuh Pangkur was the dimensions of faith, fear of God, and noble character, especially in the sub-elements of religious, personal, and state morals. In the global diversity dimension, there was an example that corresponds to the sub-elements of communication and interaction between cultures and social justice. The sub-element of collaboration which was the part of teamworks was also shown in the serat Wedhatama. In the independent dimension there was an example of self-understanding and the situation handling aspect. In addition, there was also a sub-element of thougts reflection and decisions process as part of the critical thinking dimension. Further research on Javanese moral values as a reinforcement of the Profil Pelajar Pancasila in the other serat Wedhatama’s pupuh or other Javanese literary still needs to be conducted in order to make a contribution to the education fields and to preserve the Indonesian noble heritage.